(untitled) (Perner’s Contacts, 2012)
The bistatic radar forms a basic part of multistatic radar systems for Air Traffic Control. The effort in this article is to provide the inside and make basis for future research of the bistatic radar clutter. There is a clutter scenario defined, and a very general geometry is used. For that the bistatic radar clutter power equation is derived and used for computation of some of interesting parameters such as a bistatic radar effective clutter cross section, a mean clutter power and clutter reflectivity. The developed model for the bistatic clutter is demonstrated on signals of a FM radio receiver base station.